RISK FACTORS AND SURGICAL APPROACH FOR PARS PLANA VITRECTOMY OF POSTERIORLY DISLOCATED INTRAOCULAR LENSES - WAQAS , HM; KHAN, SS; AADIL , N; FATIMA, M; JAFRI , SHR; MANZOOR, A (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Ophthalmology, Nishtar Medical Hospital, and Bakhtawar Amin Trust Hospital from January 2022 to January 2023 to evaluate risk factors and surgical approach for posterior dislocation of the intraocular lens into vitreous requiring pars plana vitrectomy. A total of 30 eyes of 30 patients (20 male and 10 female) were included in the study. Standard PPV vitrectomy was performed in all patients. The Iris fixation technique was used in patients having a 3-piece lens design. A sclera fixation technique was performed to secure the lens and prevent it from falling onto the retina. IOL (Intra-Ocular Lens) was exchanged in eyes in which it was previously damaged. Results showed that in 28 (93.3%) eyes, the original lens was conserved and positioned on the scleral wall, iris, or both. The existing lens could not be preserved in 2(6.6%) eyes. 92.1% of cases had a single risk factor for IOL dislocation. After surgery, uncorrected visual acuity (UCVA) improved from 20/400 on the initial visit to 20/80 on the final (P=0.001). UCVA remained unchanged in 3 (10%) patients and improved in 27 (90%) patients. It can be concluded that the incidence of posterior IOL dislocation has been increasing. Intravitreal substance injections, myopia, and previous vitrectomy are the major risk factors. In most cases, the existing lens can be preserved and secured in the posterior chamber through pars plana vitrectomy.